The influence of liveworksheets media in social science on elementary school students' concept understanding - Harmawati , Harmawati; Sadiah, Tia Latifu; Syafiqa , Zahra (Universitas Ahmad Dahlan, 2025)
The integration of digital technology in education has become increasingly important to foster students’ active engagement and deeper understanding of subject matter. In elementary Social Science learning, traditional approaches are often limited in providing interactive and student-centered experiences. This study aimed to examine the effect of Liveworksheets, an interactive digital learning platform, on students’ conceptual understanding in Social Science. A quasi-experimental design with a pretest–posttest control group was implemented at Dawuan Tengah VI Public Elementary School during the 2024/2025 academic year. The experimental group was taught using Liveworksheets, while the control group received conventional instruction. Students’ conceptual understanding, defined by their ability to identify, classify, and explain Social Science concepts, was assessed using validated pretest and posttest instruments. Data were analyzed through normality and homogeneity testing, followed by independent-sample t-tests. The findings revealed that the experimental group achieved significantly higher improvements in conceptual understanding compared to the control group (t = [insert value], p < 0.05). These results confirm that interactive digital platforms can effectively enhance cognitive engagement and mastery of concepts in Social Science learning. This study contributes to the growing body of research on digital pedagogy by highlighting the potential of Liveworksheets to support student-centered practices, while also recommending further investigations in broader educational contexts with larger sample sizes.